Barrow Old Hall and Twiss Green : investigations of two sub-manorial estate centres within the townships of Bold and Culcheth in the hundred of Warrington 1982-87 - Garner, D. J. (Archaeopress archaeology., 2018)
This work presents results of excavations at the moated sites of Barrow Old Hall and Twiss Green, in Warrington, North West England, including evidence for possible aisled halls at both sites, as well as a significant assemblage of medieval and early post-medieval pottery.